Use of seed vigor tests for detection of intracultivar variability in sweetpepper - Fernandes, Heloisa Santos; Nedel, Jorge Luiz; Galli, José (Pesquisa Agropecuaria Brasileira, 1999)
In order to check the hypothesis of intracultivar polymorphism for vigor in sweetpepper (Capsicum annuum L.), seeds from a single lot of the cultivar Ikeda were submitted to four seed vigor tests, namely: cold test, germination rate index, accelerated aging and seedling vigor classification. Vigorous and less vigorous seedlings were separated by each test and transplanted to a greenhouse where the plants were allowed to produce seeds (S1). As a second step, the seeds from low and high vigor seedlings were resubmitted to the test by which they were originally selected and compared to a check treatment, where selection was not made. Further, only the S1 seeds produced by the plants selected through the cold test were conducted to a second generation in order to verify possible selection gain. After data analysis it was concluded that: a) there are strong evidences indicating individual vigor variation within the seed lot of the cv. Ikeda used; b) the evidences lead to the indication that the variation has, at least, one genetic component which may be used for breeding and seed quality improvement purposes, and c) the cold test was the most efficient for detection of individual vigor difference in the seed population.
Keywords: breeding; germination; polymorphism; cold test